2015
DOI: 10.1175/jpo-d-14-0199.1
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Striations to the Eddy Energy Budget and Mixing: Diagnostic Frameworks and Results in a Quasigeostrophic Barotropic System with Mean Flow

Abstract: Low-frequency oceanic motions have banded structures termed ''striations.'' Since these striations embedded in large-scale gyre flows can have large amplitudes, the authors investigated the effect of mean flow on their directions as well as their contribution to energetics and mixing using a b-plane, barotropic, quasigeostrophic ocean model. In spite of the model simplicity, striations are always found to exist regardless of the imposed barotropic mean flow. However, their properties are sensitive to the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 65 publications
0
48
0
Order By: Relevance
“…Surface eddy diffusivities from the F-N theory agree with those from altimetry (e.g., Ferrari and Nikurashin 2010;Klocker and Abernathey 2014;Bates et al 2014). The F-N theory also captures the three-dimensional structure of float-based eddy diffusivities in the intense Kuroshio Extension jet area (Chen et al 2014). On the other hand, the theory appears to break down in regions where large topographic gradients occur (e.g., Griesel et al 2010;Naveira-Garabato et al 2011;Chen et al 2014).…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Surface eddy diffusivities from the F-N theory agree with those from altimetry (e.g., Ferrari and Nikurashin 2010;Klocker and Abernathey 2014;Bates et al 2014). The F-N theory also captures the three-dimensional structure of float-based eddy diffusivities in the intense Kuroshio Extension jet area (Chen et al 2014). On the other hand, the theory appears to break down in regions where large topographic gradients occur (e.g., Griesel et al 2010;Naveira-Garabato et al 2011;Chen et al 2014).…”
Section: Introductionmentioning
confidence: 94%
“…The F-N theory also captures the three-dimensional structure of float-based eddy diffusivities in the intense Kuroshio Extension jet area (Chen et al 2014). On the other hand, the theory appears to break down in regions where large topographic gradients occur (e.g., Griesel et al 2010;Naveira-Garabato et al 2011;Chen et al 2014). Bates et al (2014) found that the F-N theory is also not effective in capturing the observed vertical structures of eddy diffusivities from the U.S./U.K.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations